2015
DOI: 10.1002/wsb.590
|View full text |Cite
|
Sign up to set email alerts
|

Teaching wildlife techniques to millennials with a flipped classroom

Abstract: Millennials prefer to learn by working in groups, using technology, engaging in real-world issues, and discussing course content. To accommodate and engage these learning preferences, I modified the traditional Wildlife Techniques lecture and lab structure by "flipping" the class. I placed lectures and instructional videos online and used class time for discussion and problem-solving. Evaluating students' perceptions of this approach revealed that they clearly found discussion groups helpful and preferred them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…The majority of our student cohorts were millennials students who were born between the 1980s and 1990s. A number of studies have shown the effectiveness of flipped classrooms and their acceptance by millennial students in the fields of wildlife, family, and consumer services [28,29]. The key issue for this age group is their familiarity and reliance upon technology based resources and their appreciation of the flexibility these resources provide for self-directed student learning.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of our student cohorts were millennials students who were born between the 1980s and 1990s. A number of studies have shown the effectiveness of flipped classrooms and their acceptance by millennial students in the fields of wildlife, family, and consumer services [28,29]. The key issue for this age group is their familiarity and reliance upon technology based resources and their appreciation of the flexibility these resources provide for self-directed student learning.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of many constraints on field activities, many ecological‐based classes are now conducted locally (e.g., on or around campus) during regularly scheduled class laboratories (Fleischner et al., 2017; McCleery et al., 2005). While it is possible to create meaningful field experience under these conditions (McCleery, 2015; McCleery et al., 2005), the growing demands on students time (course work, family, jobs, personal, internships, student clubs) has limited some students ability to attend courses that extend over multiple periods (Lei, 2010). Regular field‐based laboratory experiences also provide few alternatives for missed assignments and lack the flexibility students prefer in their schedules (McCleery, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible to create meaningful field experience under these conditions (McCleery, 2015; McCleery et al., 2005), the growing demands on students time (course work, family, jobs, personal, internships, student clubs) has limited some students ability to attend courses that extend over multiple periods (Lei, 2010). Regular field‐based laboratory experiences also provide few alternatives for missed assignments and lack the flexibility students prefer in their schedules (McCleery, 2015). In addition, generational shifts in student background and comfort with nature have left an increasing number of urban and suburban students daunted, disinterested, or unable to understand the relevance in field‐based experiences (Cotton, 2009; Fleischner et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millennials prefer to learn using technology and discussing course content (McCleery, 2015). They prioritize work-life balance more than previous generations and expect it earlier in life (Smola & Sutton, 2002).…”
Section: How Millennials Learnmentioning
confidence: 99%